Granadas de ítrio e ferro (YIG) usadas como catalisadores na síntese de acetofenona - Pinheiro, André Luis Gadelha (2020)
Iron-based catalysts containing yttrium garnet structure (YIG) were synthesized via sol-gel method and applied as catalysts in the oxidation of ethylbenzene (EB) in the presence of hydrogen peroxide (H2O2). Two series of solids were obtained, namely, YIG-Nix and YIG-Znx where the letter x indicated the Ni and Zn contents varying from 0,01 to 0,05. These solids were characterized by various physicochemical techniques such as XRD, SEM-EDS, EPR, XPS Raman and FTIR spectroscopy and N2 adsorption-desorption isotherms. The catalytic evaluation was in the oxidation of ethylbenzene in the presence of H2O2 and acetone as solvent at 50 °C. Initially, the EB to H2O2 molar ratio was 1, using 100 mg of catalyst. Variations in the reaction temperature, reaction time, EB to H2O2 molar ratio, type of solvent and substrate were carried out. According to the XRD and Raman spectroscopy results, the Y3Fe5O12 was the only phase obtained for YIG and YIG-Zn series. This indicated that zinc was incorporated to the YIG structure, independently of its content. For YIG-Ni series, the Y3Fe5O12 phase was observed in the YIG-Ni5 along with the -Fe2O3 as extra-framework specie. All solids are poorly porous due to the elevated calcination temperature e.g., 900 °C, to prepare the materials, all of them possessing a spherical and rod-shaped morphology. The selective oxidation of ethylbenzene using hydrogen peroxide as oxidant revealed that all solids were active in the short-term stability runs. Variations in the reaction’s conditions suggested that the reaction temperatures studied, EB to H2O2 molar ratios, type of solvents and substrates greatly influenced the catalytic performance. For example, pure YIG displayed approximately 40.0% of ethylbenzene conversion within 6h of reaction and selectively produced acetophenone, 2-phenyletanhol and products of acetophenone condensation and ethylbenzene oligomers at T=50 °C, EBH2O2 =1, using acetone as solvent and EB as substrate. The solids of the YIG-Ni series showed better catalytic activities, compared to those of YIG-Zn series. A superior catalytic performance of the catalysts was observed as the Ni content increases from 1 to 5% and this was attributed to the synergistic effect of Ni and Fe3+ Fe2+ pairs. For YIG-Zn series, the catalytic performance is much lower at high Zn content due to the leaching of the active sites to the reaction media According to MEV-EDS, XPS and EPR results, the affinity of the Fe2+Fe3+ species with those of Ni2+ ones for the ethylbenzene molecule allowed the reaction to give an EB conversion of 77% with a good production of acetophenone over the YIG-Ni3 catalyst compared to other binary and ternary solids.